Malaysia's defeat of armed communism the Second Emergency, 1968-1989 - Ong, Weichong (Routledge studies in the modern history of Asia, 2015)
The Malayan Communist Party's (MCP) decisive defeat in 1960 led many academics and counterinsurgency (COIN) experts to overlook the resurrection of its armed struggle in 1968. Most scholars continue to regard the so-called 'Second Emergency' in Malaysia (1968-1989) as a non-event, and most of the recently published work on the MCP tends to focus on the earlier Malayan Emergency (1948-1960). This book looks at the Second Emergency through recently released archival material from the National Archives in London, the National Australian Archives and the Australian War Memorial, as well as interviews with military and diplomatic officers from the UK and Thailand